APLIKASI SPIRITUAL CARE TERHADAP PERILAKU BERISIKO ANAK JALANAN DI KABUPATEN JEMBER - Trisna Vitaliati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
Research Objectives: This study aims to identify the effect of spiritual care on the risk behavior of street children in Jember Regency. Method: The research method used was a quasi-experimental approach to the pre-post test design using a risk behavior questionnaire, conducted on 30 street children. Data analysis was carried out univariately and bivariately. Results: The results showed a mean score of changes in risk behavior in street children. Wilcoxon matched pairs test results obtained Z count -4,802> t and asymp sig. (2-tailed) 0,000 <α = 0.05, so it can be concluded that the implementation of spiritual care significantly influences changes in risk behavior in street children. Conclusion: the implementation of nursing care with a spiritual care approach effectively prevents risky behavior in street children, so this program is recommended to be applied to street children as part of the street children's empowerment program.